2019
DOI: 10.3892/etm.2019.8217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and association analysis of persistent low‑level HBsAg expression in a physical examination population with HBV infection

Abstract: Certain patients with hepatitis B virus (HBV) infection present with persistently low levels of serum hepatitis B surface antigen (HBsAg) and have been indicated to have low rates of HBV nucleic acid replication. To explore the serological and molecular epidemiological characteristics of HBV population with low-level HBsAg in the present study, associated serum markers and virologic genotype detection were performed accordingly. Determination of HBV markers was performed using a chemiluminescence immunoassay f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…As expected, TGF-β1 has a strong association with HBV replication and HBV related liver diseases (10,11). TGF-β1 has been demonstrated to serve important roles in HBV induces liver fibrosis via the TGF-β1/miR-21-5p pathway WENTING LI 1,2* , XIAOLAN YU 2,3* , XILIU CHEN 4* , ZHENG WANG 5 , MING YIN 2,6 , ZONGHAO ZHAO 1,2 and CHUANWU ZHU 7 hepatic stellate cell (HSC) activation, which is a key event in liver fibrosis (11,12). Accumulating evidence suggested that HBV infection may promote TGF-β1 production by hepatocytes, which in turn activates HSCs and accelerates liver fibrosis (13)(14)(15).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…As expected, TGF-β1 has a strong association with HBV replication and HBV related liver diseases (10,11). TGF-β1 has been demonstrated to serve important roles in HBV induces liver fibrosis via the TGF-β1/miR-21-5p pathway WENTING LI 1,2* , XIAOLAN YU 2,3* , XILIU CHEN 4* , ZHENG WANG 5 , MING YIN 2,6 , ZONGHAO ZHAO 1,2 and CHUANWU ZHU 7 hepatic stellate cell (HSC) activation, which is a key event in liver fibrosis (11,12). Accumulating evidence suggested that HBV infection may promote TGF-β1 production by hepatocytes, which in turn activates HSCs and accelerates liver fibrosis (13)(14)(15).…”
Section: Introductionmentioning
confidence: 61%
“…A recent study from China also showed that Persistent Low Level of Hepatitis B Virus (LLV) widely existed in HBV infected patients despite antiviral therapy ( 4 ). Moreover, despite the widespread use of strong antiviral treatments, patients with HBV infection still inevitably progress to liver fibrosis, or even liver cirrhosis ( 5 ). However, the mechanism underlying HBV-induced liver fibrosis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the prevalence of smear-positive tuberculosis, which approximates 59/100,000, is one of the highest in the world ( Li et al, 2017a ). And also infection with HBV is most prevalent in China ( Dai et al, 2019 ). Therefore, the patient’s concern is truly a major clinical problem.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were all from the physical examination center of the hospital, and were found during the normal physical examination. Definition of chronic ASC is characterized by the presence of positive serum HBsAg for more than 6 months, normal serum amino transferase levels and no evidence of liver cirrhosis (LC) or hepatocellular carcinoma (HCC) based on the clinical criteria and ultrasound examination ( 31 ). The study was carried out in accordance with the principles of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%